2013
DOI: 10.3390/arts2040383
|View full text |Cite
|
Sign up to set email alerts
|

The Perception of Depicted Motion

Abstract: Everyone knows that you can read a galloping horse in a still image as galloping. This paper asks how it is that we perceive motion in pictures. It considers perception of real motion in point-light experiments and the perception of motion in stills via the work of various psychologists, in the course of which it raises theoretical questions about the nature of visual perception. It then offers a detailed examination of knowledge regarding neural substrates for both real and depicted motion perception. Finally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 88 publications
(79 reference statements)
0
7
0
Order By: Relevance
“…Second, the utilization of static images implying motion showing either the starting or end point of the corresponding dynamic event has been previously debated (e.g., Acik et al., 2014; Jellema & Perrett, 2003; Urgesi, Moro, Candidi, & Aglioti, 2006), with no firm conclusions. In our study, given the nature of the movement selected (i.e., dance step), it was thought to be depicted better at the peak of the action, which happens to be the end posture (see also Dobrez, 2013, on the role of asymmetry in still images depicting movement). Our choice is in accordance with other studies that have also utilized the end posture and have reported an effect on timing estimates (e.g., Bueno & Nather, 2012; Nather & Bueno, 2011, 2012a; Nather et al., 2011).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Second, the utilization of static images implying motion showing either the starting or end point of the corresponding dynamic event has been previously debated (e.g., Acik et al., 2014; Jellema & Perrett, 2003; Urgesi, Moro, Candidi, & Aglioti, 2006), with no firm conclusions. In our study, given the nature of the movement selected (i.e., dance step), it was thought to be depicted better at the peak of the action, which happens to be the end posture (see also Dobrez, 2013, on the role of asymmetry in still images depicting movement). Our choice is in accordance with other studies that have also utilized the end posture and have reported an effect on timing estimates (e.g., Bueno & Nather, 2012; Nather & Bueno, 2011, 2012a; Nather et al., 2011).…”
Section: Discussionmentioning
confidence: 91%
“…This is a tangible example of an image implying motion. The use of a single image to suggest movement has been of great interest for both artists (e.g., Dobrez, 2013; Nather & Bueno, 2012c; Reason, 2004) and scientists (e.g., Cutting, 2002; Nather & Bueno, 2008). The seminal memory tests of Freyd and coworkers (Freyd, 1983; Freyd & Finke, 1984) have illustrated the dynamic nature of mentally extrapolating (i.e., “representational momentum”) an action that is implied in frozen-action photographs (see Freyd, 1987; Thornton & Hubbard, 2002, for reviews).…”
Section: Introductionmentioning
confidence: 99%
“…), but from the use of different techniques playing with lines, shapes, and directions on the bi-dimensional surface [ 46 ]. For example, patterns with acute angles presented as diagonals or wedge shapes in oblique position [ 47 ], shapes with curvy and wavy lines [ 48 ], multiple and successive stroboscopic images superimposed on a flat surface [ 49 ], might convey the sense of movement.…”
Section: Introductionmentioning
confidence: 99%
“…A static picture can be seen as a 'freeze frame' of an action, with implied motion (Goldstein, 2007;Dobrez, 2013). In the Gericault 1821 painting The Epsom Derby (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Realistic or not, of interest, Arnheim (1974), a keen Gestalt theorist, argued that the dynamic characteristics (Dobrez, 2013;Hubbard and Ruppel, 2017) perceived in a picture derive from the lines, shapes and directions on the bidimensional surface rather than from familiarity with real postures. For example, limbs with acute angles, presented as diagonals, might suggest motion.…”
Section: Introductionmentioning
confidence: 99%